KORELASI ASPEK DEMOGRAFI DAN AKSESIBILITAS LAYANAN KESEHATAN TERHADAP PENGGUNAAN KONTRASEPSI JANGKA PANJANG - Lestari, Wa Ode Sri Wati; Pratami, Intan Monik; Sari, Novi Maya; Firna, Fransiska (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The high rate of population growth that still occurs in a number of provinces in Indonesia, as well as the imbalance of the age structure of the population, is a major issue in population management and the implementation of family planning programs nationally. The purpose of the study was to determine the correlation of demographic aspects and accessibility of health services to the use of long-acting contraceptives. The research design used in this study was cross sectional. The research was conducted in Sungai Bahar sub-district in September 2024. The study population was women of childbearing age who were active family planning acceptors in Sungai Bahar District, Muaro Jambi Regency, which amounted to 3,156 people. The sample amounted to 90 people. The sampling technique used in this study was Simple Sampling. Data analysis was carried out univariate and bivariate. The results showed a relationship between education (p value: 0.043) and accessibility of health services (p value: 0.024) on the use of Long-Term Contraceptive Methods. It is recommended for couples of childbearing age to diligently seek information related to family planning services, especially about the Long-Term Contraceptive Method (MKJP) so that they have extensive knowledge about the concept of family planning and can use contraceptives that suit their needs.Keywords: Long-Acting Contraceptive Method, Education, Population.